2021
DOI: 10.3390/w13182473
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the First Negative Ion-Based Cloud Seeding and Rain Enhancement Trial in China

Abstract: Negative ion-based cloud seeding has been shown to be an effective means in the laboratory. China’s first negative ion-based cloud seeding outfield trial was conducted in the northwestern interior. This paper briefly introduces the principle of the ion-based precipitation enhancement, and the trial location is described. The design of the ionization system and meteorological monitoring network are presented. The implementation plan of the outfield trial is explained. In addition, the evaluation of experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Weather modification in China has become an essential basic public welfare undertaking for the coordinated development of state and local governments after years of development [1][2][3]. Many studies have shown that a successful weather modification operation is inseparable from a comprehensive understanding of the cloud features [4][5][6][7]. Therefore, the accurate forecast of cloud features in the atmosphere is the key to the efficient development of cloud water resources and artificial rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…Weather modification in China has become an essential basic public welfare undertaking for the coordinated development of state and local governments after years of development [1][2][3]. Many studies have shown that a successful weather modification operation is inseparable from a comprehensive understanding of the cloud features [4][5][6][7]. Therefore, the accurate forecast of cloud features in the atmosphere is the key to the efficient development of cloud water resources and artificial rainfall.…”
Section: Introductionmentioning
confidence: 99%